THE ROLE OF PLANT POLYPHENOLS IN THE HEALTH PRESERVATION: EFFECTS ON HUMAN CARDIOMETABOLIC FUNCTION - Gostimirović, Miloš; Rajkovic, Jovana; Djokic, Vladimir; Terzic, Dusko; Putnik, Svetozar; Gojkovic-Bukarica, Ljiljana (Medicinski podmladak, 2021)
Although the continuous improvement of diagnostic possibilities and the organizational structure of the Health system contributes to the reduction of the complicated courses of diseases, modern socio-economic and environmental stressors, life habits and increased fluctuation in the psychological functioning of the individual have a great influence on the overall burden of human diseases. Today, etiological factors and pathogenic mechanisms of many diseases are known, thus enabling their continuous and timely pharmacotherapy. However, for progressive diseases or those associated with the many complications, pharmacological treatment can lead to the side effects, so preventive measures are highlighted as the main strategy in the management of such diseases, especially in chronic non-communicable diseases such as cardiovascular diseases (CVDs). One of the preventive measures is timely and qualitative supplementation of the diet with beneficial micronutrients and oligoelements. Their main sources are represented in plant fibers that synthesize biologically active substances with a polyphenolic ring in their structure, called natural polyphenolic compounds (NPC). Decades of NPC research have brought new insights into the potential modification of existing pharmacotherapy of many diseases. Today, it is known that many polyphenols have an optimal pharmacological profile with cardioprotection and at the center of their overall effects. Research into the mechanisms of polyphenolic action is exhaustive, their interactions with numerous subcellular structures have been described, and they are refered as promising molecules, with the potential to modify key pathogenetic elements that lead to the progression of many diseases. So far, their numerous effects on endothelium, smooth muscle cells and lipid cells involved in the process of atherogenesis are known, their antidiabetic, antioxidant, anti-inflammatory and immunomodulatory properties have been proven, and the synergy with the intestinal microbial populations has recently been known to contribute to their beneficial effects. This paper has the aim to point out the most important mechanisms that NPC use to improve general functionality of the organism by stimulating its defense capacity, prolonging cell life and delaying the overall aging of the organism. As the most important cardioprotective nutrients, special focus is given to their beneficial effects on cardiovascular and metabolic function.
Keywords: plant polyphenols; general biological properties; cardiovascular diseases; cardiometabolic effects